The Effect of Compost and NPK Fertilizers on The Growth and Yield of Shallots - Yohanes Parlindungan Situmeang; Ida Bagus Komang Mahardika; Antonius Petrus Lalu Mato (Agriwar Journal, 2022)
This study aims to determine the effect of compost fertilizer and NPK fertilizer on the growth and yield of Shallots. This research was conducted at the Local Waste Processing Site, Kusamba Village, Klungkung. This experiment used a randomized block design (RBD) with a factorial pattern consisting of 2 factors. The first factor was the dose of compost (T) consisting of 3 levels, namely: 5-ton ha-1 (T1), 10-ton ha-1 (T2), and 15-ton ha-1 (T3). The second factor is the dosage of NPK fertilizer (M) consisting of 3 levels: (M1) 150 kg/ha-1, (M2) 300 kg/ha-1, (M3) 450 kg/ha-1. The interaction between compost treatment and NPK had a significant (P<0.05) to very significant (P<0.01) effect on all observed variables except fresh weight per clump. The highest fresh weight of tubers was obtained from the interaction between compost 5 tons ha-1 and NPK 150 kg ha-1 (T1M1) giving the highest fresh weight of tubers per clump, 41.44 g, significantly different or an increase of 45.13% compared to the fresh weight of tubers. The lowest per clump was the interaction of 15-ton ha-1 compost with NPK 450 kg ha-1 (T3M3), which was 31.25 g.